Magnocellular based visual motion training improves reading in Persian - Ebrahimi, L; Pouretemad, H; Khatibi, A; Stein, J (Springer Nature, 2019)
The visual magnocellular system is thought to play a crucial role in learning to read. Here therefore, we examined whether magnocellular based training could improve reading in children with visual reading problems. The participants were 24 male primary school students aged between 9-11 (Mean = 9.76, SD = 0.59) with specific reading difficulty. Experimental and control groups were matched for age, sex, educational level, IQ, reading abilities (measured by APRA), magnocellular performance as assessed by a random dot kinematogram (RDK) paradigm and recordings of their saccadic eye movements. The experimental group received twelve magnocellular based visual motion training sessions, twice a week over 6 weeks. During the same period, the control group played a video game with the help of a practitioner. All measures were made just prior to the training and were repeated at the 6th, 12th training session and one month later. The experimental group showed significant improvements in magnocellular function, visual errors and reading accuracy during the course of intervention. Follow-up assessment confirmed that these effects persisted one month later. Impaired magnocellular functioning appeared to be an important cause of poor reading in Persian. Hence magnocellular based training could help many children with specific reading difficulties. Also testing magnocellular function could be used as screening tool for detecting dyslexia before a child begins to fail at school.